Diversity and potential contribution of wild edible plants to sustainable food security in North Wollo, Ethiopia - Ahmed Hassen (Society for Indonesian Biodiversity, 2021)
Hassen A. 2021. Diversity and potential contribution of wild edible plants to sustainable food security in North Wollo, Ethiopia. Biodiversitas 22: 2501-2510. Rural communities in different parts of the world use WEPs as supplementary food to increase dietary diversity. The findings of this study showed that 40.7% of the participants were food insecure in the study area. They are significantly dependent on WEPs when sudden drought exists. There were no significant studies conducted about ethnobotany in the study area. Therefore, this study was the first attempt to survey the perception of local people towards the potential resources of WEPs for sustainable food security, and conservation and management trends in North Wollo. Data was collected using semi-structured interviews (135 participants), tour-guided field observation, and focus group discussion (45 participants) to get relevant and adequate data. Descriptive statistics, one-way ANOVA, and preference ranking were used to analyze and interpret the quantitative data. A total of 66 locally available WEPs belong to 30 families found in the study area. Respondents’ preference revealed that O. ficus-indica, Z.spina-christ, C. spinarum, F. sur, and U. sinesis were ranked first, second, third, fourth, and fifth, respectively. Hence, this study will provide relevant information for policy-makers and managers to combat food insecurity in the study area.